PENGGUNAAN SEPIC CONVERTER PADA PENGEREMAN REGENERATIF MOTOR BRUSHLESS DIRECT CURRENT DENGAN SUPERKAPASITOR - Rakha Ghilman Fakhruddin Yusuf; Waru Djuriatno; n/a Wijono (Jurnal Mahasiswa TEUB, 2023)
This research is to explain how to use the SEPIC Converter for regeneratif braking using a supercapacitor and its impact on the BLDC motor regeneratif braking process and the supercapacitor charging process. This research was conducted by simulating a BLDC motor regeneratif braking system with a supercapacitor load on the PSIM software. Tests were carried out by varying the duty cycle value of the MOSFET SEPIC converter with a value between 10% to 80% with binding variabels in the form of motor braking time, braking torque, converter input voltage and current, and converter output voltage and current. The results obtained in this study are, the greater the duty cycle value, the faster the braking of the BLDC motor will be. This is indicated by the braking torque which appears to be getting bigger. In addition, the duty cycle value also affects the working system of the converter, where when duty cycle value below 50% making it work as a buck converter or reducing voltage, and if the duty cycle value is below 50% it will make the converter work as a boost converter or voltage booster. Efficiency converters range from 90.8% to99.9% with a maximum efficiency value of 50% duty cycle, and a minimum efficiency value of 80% duty cycle. The duty cycle value also affects the supercapacitor charging process, where the smaller the duty cycle value makes more energy stored in the supercapacitor, due to the greater current flowing.Keywords : BLDC Motor, Regeneratif Braking, SEPIC converter, supercapacitor.